Penerapan Metode FIFO Sistem Informasi Manajemen Stok Obat pada Gudang Farmasi Dinas Kesehatan Kota Medan - Irwansyah, Rudi; Nasution , Muhammad Irwan Padli (Teknik Informatika Universitas Pamulang, 2023)
The Medan City Health Office Pharmacy Warehouse is a drug and pharmaceutical product storage facility managed by the Health Office in Medan City. This warehouse acts as a distribution center for drugs and pharmaceutical materials to meet the needs of health services in the Medan city area, which in practice still uses records that are not integrated with the system, namely still with manual recording so that inaccuracies in recording expiration dates, incoming goods, outgoing goods, drug stocks and document storage. Therefore, as a solution, the author wants to implement a drug stock distribution management information system. In building this drug stock management information system, the author applies the FIFO (First in Fisrt Out) method to ensure that drugs that enter first will be distributed first so as to reduce the risk of expiration. Furthermore, the system was developed using the waterfall system development method, which emphasizes structured stages. The results showed that the implementation of the drug distribution management information system with the FIFO method met the success criteria of each test, namely System Functionality Testing, Accuracy Testing and Effectiveness Testing. The conclusion of this research is that this drug distribution management information system is successful in reducing the risk of errors in managing drug stocks, optimizing the drug distribution process, and improving the performance of the Medan city pharmaceutical warehouse.